Critical aspects in research infrastructure management - Souyioultzoglou, Irakleitos (Homo Virtualis, 2019)
As the scholarly communication landscape is constantly evolving, the development of an ecosystem of infrastructures supporting digitally-oriented research practices becomes a necessity. This paper is a contribution to the ongoing discussion on the sustainability of digital research infrastructures∙ it describes four key operating principles and their interrelationships.